STUDI ISLAM MELALUI PENDEKATAN FENOMENOLOGI (TELAAH PEMIKIRAN ANNEMARIE SCHIMMEL) - Mahridawati Mahridawati; Samsul Bahri (STIT Darul Hijrah Martapura, 2023)
The approach to studying Islam by Charles J. Adams is divided into two main things, namely the normative or religious approach and the descriptive approach. The normative approach is an approach that is based on religious commitment, and still includes the subjective objectives of the reviewer and of course the results of the study will tend to be more subjective. The phenomenological approach that Schimmel applies in Islamic studies is a phenomenological approach that he knew from Friedrich Heiler. Implementation of this approach through systematic steps (techniques), namely examining first the phenomenon (the world of external manifestations of Islam) and then the deeper and deeper layers of human responses to God (the world of religious imagination and experience), to reach the deepest sacred essence of each religion, the center, the God, the Deus Absconditus (objective world of religion) and Schimmel has implemented it well through the intended steps.